Surface ship gravity data obtained on board the icebreaker Shirase - Yasuo Konishi; Yoichi Fukuda; Yoshifumi Nogi (National Institute of Polar Research, 2006)
A ship-borne gravity survey on board the icebreaker Shirase has been continuously conducted since JARE-27 (the 27th Japanese Antarctic Research Expedition); about 17 years of gravity data have been accumulated. Although data obtained from JARE-27 to JARE-33 have already been processed and stored in MGD77 format, data starting with JARE-34 have remained unprocessed. We newly processed the data from JARE-34 to JARE-46 to obtain free-air gravity anomalies. To attain better quality, especially in the long wavelength gravity signals, we also applied drift corrections for all the data sets since JARE-27 by employing satellite derived gravity anomalies as a reference gravity field. This report summarizes the data processing and the status of the surface ship gravity data.